2014
DOI: 10.3389/fpsyg.2014.00973
|View full text |Cite
|
Sign up to set email alerts
|

Sound Practice—improving occupational health and safety for professional orchestral musicians in Australia

Abstract: The Sound Practice Project is a 5-year study involving baseline evaluation, development, and implementation of musician-specific work health and safety initiatives. A cross-sectional population physical and psychological survey and physical assessment were conducted at the same time, with an auditory health assessment conducted later. The results were used to guide the development of a series of targeted interventions, encompassing physical, psychological, and auditory health components. This paper provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 41 publications
5
83
0
3
Order By: Relevance
“…The research into musicians’ health undertaken over the past three decades has employed mainly clinical and diagnostic approaches to identifying and understanding the multitude of problems that arise from music practice and performance, in particular in the Western classical tradition. This research has made great strides toward legitimizing the health challenges that classical musicians face and toward enabling discussion of health issues both among musicians and more widely within educational and professional contexts ( Brandfonbrener, 1986 ; Jabusch et al, 2004 ; Altenmüller and Jabusch, 2009 ; Ackermann et al, 2012 , 2014 ). Indeed, health education and provision has increased considerably within music in the intervening years (for reviews, see Chesky et al, 2006 ; Williamon and Thompson, 2006 ), although not nearly enough to match the size and scope of problems reported in the literature and driven by an agenda that is predominantly reactive rather than preventative and proactive.…”
Section: Introductionmentioning
confidence: 99%
“…The research into musicians’ health undertaken over the past three decades has employed mainly clinical and diagnostic approaches to identifying and understanding the multitude of problems that arise from music practice and performance, in particular in the Western classical tradition. This research has made great strides toward legitimizing the health challenges that classical musicians face and toward enabling discussion of health issues both among musicians and more widely within educational and professional contexts ( Brandfonbrener, 1986 ; Jabusch et al, 2004 ; Altenmüller and Jabusch, 2009 ; Ackermann et al, 2012 , 2014 ). Indeed, health education and provision has increased considerably within music in the intervening years (for reviews, see Chesky et al, 2006 ; Williamon and Thompson, 2006 ), although not nearly enough to match the size and scope of problems reported in the literature and driven by an agenda that is predominantly reactive rather than preventative and proactive.…”
Section: Introductionmentioning
confidence: 99%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…A preliminary analysis of gender differences showed a trend for females to present with poorer physical and mental health outcomes. These results were, however, not statistically signi cant and need to be studied further (48,49).…”
mentioning
confidence: 75%